Development Of Mathematics-Based Learning Media Problem-Based Android-Assisted Learning For Students Grade VIII Junior High School - As Bintang; Ali Asmar; I Made Arnawa; Edwin Musdi (JETL (Journal of Education, Teaching and Learning), 2025)
This study aims to produce teaching materials based on the Adroid-assisted problem based learning model to improve students ' mathematical problem solving skills that are valid, practical, and effective. This is motivated by the low ability to solve mathematical problems of students from SMPN 15 and Madrasah students from previous research, as well as the lack of utilization of digital Learning media in the process of learning mathematics.  The research procedure is guided by the design of Plomp development. The development Model studied by Plomp is the initial investigation phase, the development or prototyping phase, and the research phase. The population in this study is eighth grade students MTsN 1 Padang. Data collection instruments are in the form of initial investigation phase instruments with interview guidelines, student opinion questionnaires, student test sheets. Instrument for validity test. Instrument for practicality test. Instrument for effectiveness test. The results of this study showed the assessment of the material aspects by mathematics education by 86.67%, for linguists by 93.75%, and for educational technologists by 80%. Thus obtaining an average score of 86.81% with very valid criteria. Based on the results of the practical test of teaching materials by teachers and students get an average score of 86.78% with this score included in the criteria of very practical. The score obtained from the teacher's practicality test was 85% and the student's practicality test was 88.57%.